1996
DOI: 10.1002/(sici)1097-0339(199602)14:1<75::aid-dc16>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Mimics of pilomatrixomas in fine-needle aspirates

Abstract: This is a review of the fine‐needle aspirates (FNAs) of nine pilomatrixomas (PMs) found in a series of 1,500 FNAs performed on skin nodules. The objective is to determine and list the cytologic findings that might mislead the less‐experienced cytopathologist and to give him advice on how to avoid such errors. The following recommendations are made: 1) The FNAs should be carried out and the smears interpreted by the same person. 2) Clinical data, particularly age and location, are of paramount importance. 3) Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…In their review of fine-needle aspiration of eight cases of pilomatrixoma, Sanchez et al recommended the importance of examining smears stained by Papanicolaou, as well as Diff-Quik stains, since the nuclei of basaloid cells may appear unduly enlarged in the smears stained by Diff-Quik. 14 The presence of shadow cells with characteristic central pale nuclear zone has been repeatedly reported in the literature as the most important cytologic feature for the diagnosis of pilomatrixoma. However, despite their abundance in histologic sections, their detection was reported to be difficult in the cytologic smears and they may not be present at all.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In their review of fine-needle aspiration of eight cases of pilomatrixoma, Sanchez et al recommended the importance of examining smears stained by Papanicolaou, as well as Diff-Quik stains, since the nuclei of basaloid cells may appear unduly enlarged in the smears stained by Diff-Quik. 14 The presence of shadow cells with characteristic central pale nuclear zone has been repeatedly reported in the literature as the most important cytologic feature for the diagnosis of pilomatrixoma. However, despite their abundance in histologic sections, their detection was reported to be difficult in the cytologic smears and they may not be present at all.…”
Section: Discussionmentioning
confidence: 89%
“…There are several reports in the literature describing its cytologic features and addressing the main differential diagnosis and its diagnostic pitfalls. [3][4][5][6][7][8][9][10][11][12][13][14] However, a review of the literature showed that out of the 34 reported cases, a correct cytologic diagnosis was made in only 12 cases, one of these on repeat FNAB. Most of the cases were reported as carcinoma, mainly squamous cell carcinoma, or suggestive of carcinoma (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other entities to be considered in the differential diagnosis include epidermal inclusion cyst, foreign body reaction, calcinosis cutis, and lipoma. As described by Sanchez and associates, the classic cytologic appearance of pilomatrixoma consists of varying amounts of basaloid and ghost cells [9]. Basaloid cells are basophilic and are about three times the size of a lymphocyte.…”
Section: Discussionmentioning
confidence: 95%
“…The findings of fine needle aspiration biopsy can be misleading and can be mistaken for squamous cell carcinoma due to good cellularity, high nuclear/cytoplasmic ratio and anucleated squamous cells 10,18,19 .…”
Section: Discussionmentioning
confidence: 99%